THEORETICAL AND LEGAL PRINCIPLES OF IMPLEMENTING THE RIGHT OF A PERSON TO FREE LEGAL AID (Bulletin of criminological association of Ukraine, 2025)
The article substantiates that the right to legal aid is an integral part of the right to a fair trial and an important aspect of access to justice. It plays an important role in ensuring the fairness and effectiveness of the legal system, which is based on the principle of the rule of law, and also contributes to the formation of public trust in the judiciary. According to the Constitution of Ukraine, every person has the state-guaranteed opportunity to freely receive legal aid in the necessary volumes and forms (primary or secondary). This right also includes free legal aid for persons who do not have the financial opportunity to use the services of lawyers on a paid basis. It is determined that the main problems of the functioning of the BPD institute include the following: 1) limited access to services in remote regions; 2) insufficient awareness of the population due to the low level of legal culture; 3) overload of lawyers; 4) insufficient funding; 5) insufficient coordination between state bodies. Thus, despite the fact that modern challenges and the development of digital technologies contribute to expanding the possibilities of receiving primary legal aid remotely, it is important to ensure proper technical and forensic support in all centers, bodies and institutions, to create conditions for the uninterrupted operation of technical equipment and digital technologies, etc. It is emphasized that post-war reconstruction still makes these issues relevant, and therefore it is important to continue studying them.
Keywords: legal aid; human right to protection; representation; protection; center for providing free legal aid